Cultivation of the polyextremophile Cyanidioschyzon merolae 10D during summer conditions on the coast of the Red Sea and its adaptation to hypersaline sea water - Villegas-Valencia, Melany; González-Portela, Ricardo E.; de Freitas, Bárbara Bastos; Al Jahdali, Abdulaziz; Romero-Villegas, Gabriel I.; Malibari, Raghdah; Kapoore, Rahul Vijay; Fuentes-Grünewald, Claudio; Lauersen, Kyle J. (Frontiers in Microbiology, 2023)
The west coast of the Arabian Peninsula borders the Red Sea, a water body which maintains high average temperatures and increased salinity compared to other seas or oceans. This geography has many resources which could be used to support algal biotechnology efforts in bio-resource circularity. However, summer conditions in this region may exceed the temperature tolerance of most currently cultivated microalgae. The Cyanidiophyceae are a class of polyextremophilic red algae that natively inhabit acidic hot springs. C. merolae 10D has recently emerged as an interesting model organism capable of high-cell density cultivation on pure CO2 with optimal growth at elevated temperatures and acidic pH. C. merolae biomass has an interesting macromolecular composition, is protein rich, and contains valuable bio-products like heat-stable phycocyanin, carotenoids, β-glucan, and starch. Here, photobioreactors were used to model C. merolae 10D growth performance in simulated environmental conditions of the mid-Red Sea coast across four seasons, it was then grown at various scales outdoors in Thuwal, Saudi Arabia during the Summer of 2022. We show that C. merolae 10D is amenable to cultivation with industrial-grade nutrient and CO2 inputs outdoors in this location and that its biomass is relatively constant in biochemical composition across culture conditions. We also show the adaptation of C. merolae 10D to high salinity levels of those found in Red Sea waters and conducted further modeled cultivations in nutrient enriched local sea water. It was determined that salt-water adapted C. merolae 10D could be cultivated with reduced nutrient inputs in local conditions. The results presented here indicate this may be a promising alternative species for algal bioprocesses in outdoor conditions in extreme coastal desert summer environments.